An Analysis of the Internet of Things Security From Data Perception - Gaddam, Raviteja; Nandhini, M (International Journal of Computer Sciences and Engineering, 2019)
As the usage of the Internet of Things (IoT) is increasing, the challenges of providing security for IoT are becoming severe. Every IoT device generates and shares the data, which plays a key role in IoT applications. To understand the IoT security, one should observe many approaches like data, communications, and applications. Among these, a view from the data side may be of much help. This paper analyses various issues in IoT security from the data approach. Authors propose a Three Perspective Model consists of Exclusive, Inclusive and End-Users Perspectives to provide IoT Security by integrating IoT architecture and Data Transmission. The Exclusive Perspective focuses on individual IoT devices, the Inclusive Perspective focus on collective IoT devices and the end-users perspective focus on IoT applications. The three perspectives focus on the secure transmission of data, authentication, privacy and the challenges against IoT applications. This paper analyses the data perspective of IoT security discusses the challenges and suggests some possible solutions for IoT security.